Hypercholesterolemia increases plasma saturated and n-6 fatty acids altering prostaglandin homeostasis and promotes endothelial dysfunction in rabbits - Medina, María Fernanda (2014)
The present study evaluatedthe plasma fatty acidlevels and thevascular prostaglandin releaseina rabbit model of early hypercholesterolemia with endothelial dysfunction. Rabbits were fed either a control diet (CD) or a diet containing 1 % cholesterol (HD) for 5-6 weeks. The level of fatty acids was measured in plasma. The levels of prostaglandin and nitric oxide (NO) released from aorta were also determined. Vascular morphology of aorta was characterized by intima and media thickness measurement. The rabbits fed with HD had higher levels of arachidonic acid (ARA) and lower levels of oleic acid (OLA). Linoleic acid (LNA) level was unchanged. PGI2 and NO were diminished and PGF2αlevels, the PGI2/TXA2 ratio and the intima/media ratio were increased in rabbits fed with HD. In conclusion, feeding a HD for a short period increased ARA plasma levels and unbalanced release of vasodilator/vasoconstrictor PG redirecting the pathway to vasoconstrictor metabolite release. These lipid metabolism alterations in addition to the reduced NO levels and the moderate changes in the vascular morphology would contribute to the endothelial dysfunction in this animal model. Therefore, the present findings support the importance ofearly correction or prevention of high cholesterol levels to disruptthe endothelial dysfunction processthat leadsto cardiovascular disease.